Incidence of cardiac interventions and associated cardiac arrest outcomes in patients with nonshockable initial rhythms and no ST elevation post resuscitation. (October 2021) - Harhash, Ahmed A.; May, Teresa; Hsu, Chiu-Hsieh; Seder, David B.; Dankiewicz, Josef; Agarwal, Sachin; Patel, Nainesh; McPherson, John; Riker, Richard; Soreide, Eldar; Hirsch, Karen G.; Stammet, Pascal; et al.
Graphical abstract: Abstract: Background: Out of Hospital Cardiac arrest (OHCA) survivors with ST elevation (STE) with or without shockable rhythms often benefit from coronary angiography (CAG) and, if indicated, percutaneous coronary intervention (PCI). However, the benefits of CAG and PCI in OHCA survivors with nonshockable rhythms (PEA/asystole) and no STE are debated. Methods: Using the International Cardiac Arrest Registry (INTCAR 2.0), representing 44 centers in the US and Europe, comatose OHCA survivors with known presenting rhythms and post resuscitation ECGs were identified. Survival to hospital discharge, neurological recovery on discharge, and impact of CAG with or without PCI on such outcome were assessed and compared with other groups (shockable rhythms with or without STE). Results: Total of 2113 OHCA survivors were identified and described as; nonshockable/no STE (Nsh-NST) (n = 940, 44.5%), shockable/no STE (Sh-NST) (n = 716, 33.9%), nonshockable/STE (Nsh-ST) (n = 110, 5.2%), and shockable/STE (Sh-ST) (n = 347, 16.4%). Of Nsh-NST, 13.7% (129) were previously healthy before CA and only 17.3% (161) underwent CAG; of those, 30.4% (52) underwent PCI. A total of 18.6% (174) Nsh-NST patients survived to hospital discharge, with 57.5% (100) of such survivors having good neurological recovery (cerebral performance category 1 or 2) on discharge. Coronary angiography was associated with improved odds for survival and neurological recovery among all groups, including those with NSh-NST. Conclusions: Nonshockable initial rhythms with no ST elevation post resuscitation was the most common presentation after OHCA. Although most of these patients did not undergo coronary angiography, among those who did, 1 in 4 patients had a culprit lesion and underwent revascularization. Invasive CAG should be at least considered for all OHCA survivors, including those with nonshockable rhythms and no ST elevation post resuscitation. Brief abstract: Out of hospital cardiac arrest (OHCA) survivors with ST elevation and/or shockable rhythms benefit from coronary angiography and revascularization. Nonshockable cardiac arrest survivors with no ST elevation have the worst prognosis and rarely undergo coronary angiography. Nonshockable rhythms with no ST elevation was the most common presentation after OHCA and among a small subgroup underwent coronary angiography, 1 in 4 patients with had culprit lesion and underwent revascularization. Coronary angiography was associated with high prevalence of acute culprit coronary lesions and should be considered for those with a probably cardiac cause for their arres.